2018
DOI: 10.1039/c7mt00285h
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis by ICP-MS/MS as a fast tool for cellular bioavailability studies of arsenite

Abstract: Single-cell inductively coupled plasma mass spectrometry (SC-ICP-MS) has become a powerful and fast tool to evaluate the elemental composition at a single-cell level. In this study, the cellular bioavailability of arsenite (incubation of 25 and 50 μM for 0-48 h) has been successfully assessed by SC-ICP-MS/MS for the first time directly after re-suspending the cells in water. This procedure avoids the normally arising cell membrane permeabilization caused by cell fixation methods (e.g. methanol fixation). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 16 publications
(18 reference statements)
1
26
0
1
Order By: Relevance
“…Some cells "suck in" AgNPs, the reason for the long-tailed distributions. Such tailing behaviour has been demonstrated in a previous study where the uptake of inorganic As at the single cell level was investigated, 15 and so this tailing is not characteristic for NPs but for cells in general. In both studies the cell system was not synchronized, which means that cells are in different activity cycles once the experiment is started and thus have different uptake rates and even different uptake times which might deviate from the incubation time signicantly.…”
Section: Variation Of Agnp Concentration and Incubation Time In Cell mentioning
confidence: 56%
“…Some cells "suck in" AgNPs, the reason for the long-tailed distributions. Such tailing behaviour has been demonstrated in a previous study where the uptake of inorganic As at the single cell level was investigated, 15 and so this tailing is not characteristic for NPs but for cells in general. In both studies the cell system was not synchronized, which means that cells are in different activity cycles once the experiment is started and thus have different uptake rates and even different uptake times which might deviate from the incubation time signicantly.…”
Section: Variation Of Agnp Concentration and Incubation Time In Cell mentioning
confidence: 56%
“…[11] The toxic effects of arsenic were evaluated using Chlamydomonas reinhardtii [12] and A549 cells. [13] SC-ICP-MS has also been used to detect inorganic nanoparticles or quantum dots in biological tissue and cells. [14][15][16][17] On the basis of elemental data (i. e., signal intensity and number of signals), metabolism or the transportation mechanism of nano-sized materials can be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…used SC‐ICP‐MS to evaluate the effects of Cu‐based algaecide on the toxic algae, Microcystis aeruginosa [11] . The toxic effects of arsenic were evaluated using Chlamydomonas reinhardtii [12] and A549 cells [13] . SC‐ICP‐MS has also been used to detect inorganic nanoparticles or quantum dots in biological tissue and cells [14–17] .…”
Section: Introductionmentioning
confidence: 99%
“…The principle of SC-ICP-MS technology has been introduced recently [2527]. Briefly, single cell introduction into the ICP-MS system is achieved through the use of a modified nebulizer working in conjunction with a peristaltic pump that is used to deliver small volumes of cell suspension into the spray chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [28] first introduced intact single cells into magnetic sector ICP-MS directly, and reported that the intact individual bacterium behaved like a large particle in the ICP-MS. In the following several years, SC-ICP-MS was proposed and applied for metal content analysis in multiple species, including bacteria [29, 30], algae [24, 26, 31], yeast [32], and human cancer cells [25, 33–39]. Due to the capability to sensitively and rapidly measure metal content within individual cells, SC-ICP-MS is expected to be a rapid developing powerful technology with an enormous potential for applications in drug development, heavy metal toxicity study, metallomics, and other life sciences and environmental researches.…”
Section: Introductionmentioning
confidence: 99%